Lower incidence of clinical allergy with PEG‐asparaginase upfront versus the sequential use of native E. coli asparaginase followed by PEG‐ASP in pediatric patients with acute lymphoblastic leukemia. Issue 5 (16th August 2021) - Mesegué, Montserrat; Alonso‐Saladrigues, Anna; Pérez‐Jaume, Sara; Comes‐Escoda, Ariadna; Dapena, José Luís; Faura, Anna; Conde, Nuria; Català, Albert; Ruiz‐Llobet, Anna; Zapico‐Muñiz, Edgar; Camós, Mireia; Rives, Susana
Abstract: Asparaginase (ASP) is an essential component for the acute lymphoblastic leukemia (ALL) treatment, but toxicities, such as allergy, frequently limit its use. Although the potentially lower PEG‐ASP formulation immunogenicity, few studies with conflicting results have compared the allergy incidence between Escherichia coli ‐ASP and PEG‐ASP in the same protocol. We aimed at comparing the allergy incidence in children receiving native E. coli ‐ASP versus PEG‐ASP within the same clinical protocol (Spanish Society of Pediatric Hematology and Oncology ALL‐SEHOP‐PETHEMA 2013). One hundred and twenty‐six children (1–19 years) diagnosed with ALL from 2013 to 2020 were included. Patients in group 1 received a sequential scheme of native E. coli ‐ASP 10, 000 IU/m 2 intramuscularly (IM) followed by PEG‐ASP 1000 IU/m 2 IM. Patients in group 2 received PEG‐ASP 1000 IU/m 2 IM upfront. Clinical allergy incidence was compared between both groups. Serum ASP activity (SAA) was measured in a subgroup of patients, and silent inactivation was recorded. The cumulative incidence of clinical allergy was significantly higher in group 1 (native followed by PEG‐ASP) than in group 2 (PEG‐ASP upfront), 24.7% versus 4.1% ( p  = 0.0085). Adequate ASP activity was achieved with PEG‐ASP 1000 IU/m 2 dose in most patients (median SAA 412.5 and 453.0 IU/L at days 7 and 14). The incidence of silent inactivation in PEG‐ASP upfront patients was very low. PEG‐ASP‐used upfront was associated with a lower incidence of clinical allergy than that observed in the sequential use of native E. coli ‐ASP followed by PEG‐ASP. PEG‐ASP at 1000 IU/m 2 was effective in achieving enough ASP activity in most patients.